Studying Cyberspace and Culture: A Review on the Book Cyberspace, Society and Culture - Seyyed Ahmad Askari; Ehsan Shahghasemi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The emergence of the “cyberspace” and the simultaneous expansion of information and communication industries have brought about huge changes in classical concepts and social and cultural structures. One of the works that has studied this subject and issues of cyberspace in Iran has been the book Cyberspace; The Society and Culture by Seyed Abolhassan Firouzabadi, who is the head of the Iranian National Center of Cyberspace and one of the key Iranian policymakers for the Internet in Iran. This article has endeavored to review and introduce this work and then tap into the fundamental discussions on the cyberspace, culture and power to re-review and re-read it and bring examples to show this book needs theoretical and methodological improvements. On the surface, the book lacks a complete content list and a final conclusion section; works cited are dated, and there are some word usages. The book also suffers from a lack of scrutiny, and structurally speaking, the book is fragmented and loosely.